The Effect of Suture Simulation Method on Animal Skin on Skills and Anxiety Caused by Suturing in Operating Room Students - Maryam Bahrami; Somayeh Mohammadi; mostafa Roshanzadeh; Samaneh Dehghan Abnavi; Ali Taj; Fatemeh Maraki (Tehran University of Medical Sciences, 2023)
Background and Aim: Operating room students have experienced anxiety for various reasons that affect their educational process such as stitching. Due to the effective role of simulation in improving the education of students, this study was conducted with the aim of the effect of animal skin suturing simulation on the skill level and anxiety level of operating room students. Materials and Methods: In this study, 30 people (75%) of the samples were aged 18-25 and 10 people (25%) of them were 26-35. 10 people (25%) were men and 30 people (75%) were women. Also, in terms of marriage, 7 people (17.5%) were married and 33 people (82.5%) were single. The present quasi-experimental study was performed with a two-group plan before and after with 40 operating room students of Shahrekord University of Medical Sciences (Shahrekord, Broujen) in 2020. The samples were randomly assigned to two test and control groups using the method based on the purpose of selection. Data were collected before and after the intervention by Spielberger Anxiety Tool and Suturing Skills Questionnaire and analyzed by SPSS software and descriptive and analytical statistical tests (Chi-square test, t-test, paired t-test). Results: The t-test test showed that the mean of obvious anxiety in the intervention group (36.35±10.22) and the control group (41.15±7.92) after the intervention was not significant (P=0.346). Also, the mean hidden anxiety in the intervention group (36.65±10.47) and the control group (38.65±6.13) had no significant difference (P=0.089). The t-test test showed that there was a significant difference in sewing skills after the intervention in the two intervention groups (28.2±58.22) and the control group (23.42±3.12) (P=0.04). Conclusion: The texture of suture mannequins is very different from human skin in terms of consistency, and it does not convey the same feeling of sutures on natural skin to students. On the other hand, it is easier to enter and exit and move the needle and thread in the sheepskin, and this provides the students with the possibility of stitching more easily. Therefore, it is suggested to buy and prepare sheep skin for training students and teach them stitches on it.